AN ERROR ANALYSIS OF STUDENTS’ SENTENCES IN SIMPLE PAST TENSE OF NARRATIVE TEXT AT SMK MUHAMMADIYAH SEGERAN JUNTINYUAT - Abdulloh; Ida Yulianawati; Gina Larasaty (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Cirebon, 2023)
This research deals with the students’ error analysis in writing narrative text. Thisresearch aims to know the types of errors in writing narrative text based on Dulay’sTheory. This research used a qualitative research design. There were 31 studentsinvolved from the tenth grade of SMK Muhammadiyah Segeran Juntinyuat. The datawere taken from their writing of the narrative text. The result showed that there are fourtypes of errors made by students, namely omission, addition, misinformation, andmisordering. In the students writing there were 69 omission errors with a percentage65%, 17 addition errors with a percentage 16%, 5 misinformation errors with apercentage 5%, and 14 misordering errors with a percentage 14%. Therefore the mostdominant type of error made by students in the tenth grade of SMK MuhammadiyahSegeran Juntinyuat is omission errors with percentage 65% with the total number oferrors being 69. It can be concluded that most students were lack of understanding aboutusing simple past tense in their writing. The students did not understand the use oftenses, especially the simple past tense in writing.